Rethinking economic growth : towards productive and inclusive arab societies - International Labour Organization (Beirut International Labour Organization (ILO), 2012)
From ILO Library website: Examines the structure of and trends in Arab labour markets, investigates the labour demand for and supply of labour that determine employment and the institutional framework that determines decent work, especially social protection and social dialogue. Focuses on the development that took place mainly in the period from 1990 to 2010, when economic reforms were initiated in many Arab states
Output and employment growth -- Population, labour supply, employment and unemployment -- Quality of jobs and standards of living -- Education and skills -- Social protection -- Prospects and policy directions -- Workers' perspective Breaking with the past: a new Arab development model promoting trade union rights, industrialization, wage-led growth and decent work -- Employers' perspective Creating an enabling environment for enterprise-led growth and job creation: the role of representative national employer and business membership organizations --
Also available in Arabic:نظرة جديدة إلى النمو الإقتصادي : نحو مجتمعات عربية منتجة وشاملة On t.p. ILO Regional Office for the Arab States ; UNDP regional Bureau for Arab States
Bibliography: p. 151-154
Keywords: Economic development; ECONOMIC GROWTH; ECONOMIC DEVELOPMENT; EMPLOYMENT GROWTH; LABOUR SUPPLY; LABOUR MARKET; EMPLOYMENT CREATION; ARAB COUNTRIES